Comprehensive Study of Lithium Adsorption and Diffusion on Janus Mo/WXY (X, Y = S, Se, Te) Using First-Principles and Machine Learning Approaches - Chaney, Gracie; Ibrahim, Akram; Ersan, Fatih; Çakır, D.; Ataca, Can (ACS Publications, 2021)
The structural asymmetry of two-dimensional (2D) Janus transition-metal dichalcogenides (TMDs) produces internal dipole moments that result in interesting electronic properties. These properties differ from the regular (symmetric) TMD structures that the Janus structures are derived from. In this study, we, first, examine adsorption and diffusion of a single Li atom on regular MX2 and Janus MXY (M = Mo, W; XY = S, Se, Te) TMD structures at various concentrations using first-principles calculations within density functional theory. Lithium adsorption energy and mobility differ on the top and bottom sides of each Janus material. The correlation between Li adsorption energy, charge transfer, and bond lengths at different coverage densities is carefully examined. To gain more physical insight and prepare for future investigations into regular TMD and Janus materials, we applied a supervised machine learning (ML) model that uses clusterwise linear regression to predict the adsorption energies of Li on top of 2D TMDs. We developed a universal representation with a few descriptors that take into account the intrinsic dipole moment and the electronic structure of regular and Janus 2D layers, the side where the adsorption takes place, and the concentration dependence of adatom doping. This representation can easily be generalized to be used for other impurities and 2D layer combinations, including alloys as well. At last, we focus on analyzing these structures as possible anodes in battery applications. We conducted Li diffusion, open-circuit voltage, and storage capacity simulations. We report that lithium atoms are found to easily migrate between transition-metal (Mo, W) top sites for each considered case, and in these respects, many of the examined Janus materials are comparable or superior to graphene and regular TMDs. In addition, we report that the side with higher electronegative chalcogen atoms is suitable for Li adsorption and only MoSSe and MoSeTe can be suitable for full coverage of Li atoms on the surface. Bilayer Li adsorption was hindered due to negative open-circuit voltage. Bilayer Janus structures are better suited for battery applications due to less volumetric expansion/contraction during the discharge/charge process and having higher storage capacity. Janus monolayers undergo a transition from semiconducting to metallic upon adsorption of a single Li ion, which would improve anode conductivity. The results imply that the examined Janus structures should perform well as electrodes in Li-ion batteries.
Keywords: UMBC High Performance Computing Facility (HPCF)